Bioremediation of Ammonia and Nickel from Solutions by Viable, Killed and Immobilized Non-pathogenic Microorganisms - Elizabeth, K.M.; Kezia Rani, A. (Asian Journal of Chemistry, 2010)
Bioremediation of ammonia and nickel from artificially introduced solutions was determined by viable, killed and immobilized non-pathogenic microorganisms. The concentration of the metals used was 100 mg/mL. The concentration of sorbent used in biosorption technique was 5.0 mg/mL. The live Staphylococcus species could remove 90.7% of ammonia and 56.5% nickel at pH 7. It could remove 91.5% ammonia and 36% of Ni by biosorption and 95% ammonia and 74.3% Ni by immobilization technique indicating that it was a very potential microorganism that can remove ammonia very efficiently. There was highest percentage removal of ammonia (93.3%) by E. coli through immobilization. Live Bacillus species (BS1) could remove 78.3% ammonia and 61.4% Ni, 94.36% ammonia and 79.8% Ni by immobilization technique. Live Bacillus megaterium could remove 84.3% ammonia and 24.4% Ni, 100% ammonia and 79% Ni through biosorption technique at pH 7. The effect of pH on bioremediation was studied. The results were subjected to chi-square test to determine whether the percentage removal of these pollutants was significant or not. These results clearly indicate that bioremediation of ammonia and nickel was very efficient by all microorganisms used and they can be utilized in the treatment of industrial, agricultural and domestic wastes, where there was plenty of ammonia and nickel.